GOOD-LIVING: : ONE ANSWER TO CIVILIZATIONAL CRISIS - Sanson, César (2020)
The present article analyzes the advanced stage of thecontemporary civilizational crisis fivefold - economic, energy, food,climate and labor – which present ruptures between society and theeconomy and society and the environment. A possible response to thiscivilizational crisis and the return of a society that is sustainable withnature which present ruptures between society and the economy andsociety and the environment. A possible response to this civilizationalcrisis and the return of a society that is sustainable with nature, presentand future human needs, and a solidary ethic can be found in the conceptgood-living. Good-livinga, a millenarian concept originating fromindigenous peoples, is constructed in opposition to the western 'betterliving', which is individualistic and is done at the expense of nature.